A multi-directional synchronous pressing method for graphite crucible for lithium battery negative electrode material

CN123003287APending Publication Date: 2026-10-30NINGXIA HEXING CARBON-BASED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611228983.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本申请的目的在于提供一种锂电池负极材料用石墨坩埚多向同步压制方法,以解决如何在保留模压工艺高效率、低成本优势的同时,突破传统单向或双向压制导致的密度分布不均、各向异性明显及抗热震性能不足的问题

Benefits of technology

1、本发明通过将三种不同粒度范围(0-2 mm、0-3 mm、5-25 mm)的石墨原料分别进行研磨或破碎处理,并采用特定质量百分比(0-0.5 mm∶0.5-1 mm∶1-2 mm∶2-4 mm = 32.9∶22.6∶25.2∶19.3)的粒度级配,使粗、中、细颗粒形成最紧密堆积结构。该级配设计显著减少了颗粒间的孔隙率,可以提高压制后石墨坩埚的体积密度、抗折强度和抗压强度,从而延长了石墨坩埚在高温、强腐蚀环境下的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003287A_ABST
    Figure CN123003287A_ABST
Patent Text Reader

Abstract

The application discloses a kind of graphite crucible multi-directional synchronous pressing method for lithium battery negative material, by three different particle size range graphite raw materials are respectively ground or broken, and using specific mass percentage particle size grading, make coarse, medium, fine particle form the closest packing structure.The grading design significantly reduces the porosity between particles, can improve the bulk density, bending strength and compressive strength of graphite crucible after pressing, thereby prolong the service life of graphite crucible.Simultaneously, using multi-directional synchronous static pressure forming process, under 20MPa pressure, the paste in the die cavity is pressed into shape, can make paste in die cavity receive all-around uniform pressure stress, effectively avoid the density difference of graphite crucible bottom and sidewall caused by stress concentration.The density difference of graphite crucible wall body and bottom after pressing can be controlled within the set range, ensure more uniform thermal conductivity and thermal shock resistance in the graphitization process of lithium battery negative material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of graphite crucible pressing technology, and in particular to a multi-directional synchronous pressing method for graphite crucibles used in lithium battery anode materials. Background Technology

[0002] As the global energy structure accelerates its transformation towards cleaner and lower-carbon energy, the new energy vehicle and energy storage industries are experiencing explosive growth, directly driving the rapid expansion of the lithium-ion battery market. Graphite anode materials, as a core component of lithium-ion batteries, are seeing a continuous increase in demand. In the anode material production process, graphitization is the most energy-intensive and longest-cycle critical step, and the quality and performance of the graphite crucible, as the core container of the graphitization furnace, directly determine the sintering quality, unit energy consumption, and overall production cost of the anode material.

[0003] Currently, the forming process for graphite crucibles in the industry generally adopts traditional unidirectional or bidirectional molding techniques. Specifically, axial pressure is applied to the graphite powder inside the mold using an upper or both upper and lower pressure heads to compact it into shape. This type of process has mature equipment, is simple to operate, and is widely used in industry. However, with the downstream lithium battery industry's continuously increasing requirements for the consistency, purity, and cost control of anode materials, the inherent technical bottlenecks of traditional molding crucibles are becoming increasingly prominent. Uneven density distribution and significant anisotropy: In traditional unidirectional or bidirectional pressing processes, there is a significant gradient attenuation and sidewall friction effect when pressure is transmitted within the powder, resulting in significant differences in the green body density in different regions of the crucible wall and bottom. After graphitization, this density difference further evolves into anisotropy of material properties, affecting the uniformity of heat conduction and volume stability of the crucible during use.

[0004] Poor thermal shock resistance and short service life: Due to insufficient density uniformity and complex internal residual stress distribution, existing crucibles are prone to micro-cracks that expand rapidly under the severe thermal shock environment of repeated temperature rise and fall in graphitization furnaces, leading to cracking, slag shedding, or even scrapping. They are gradually unable to meet the needs of high-end anode material customers for long-cycle stable production and reduced furnace shutdown and replacement frequency.

[0005] Against this backdrop, how to overcome the technical bottlenecks caused by traditional unidirectional or bidirectional pressing, such as uneven density distribution, obvious anisotropy, and insufficient thermal shock resistance, while retaining the advantages of high efficiency and low cost of molding process, and develop a molding method that can realize multi-directional stress and synchronous densification of crucible body, has become a key technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] The purpose of this application is to provide a multi-directional synchronous pressing method for graphite crucibles used in lithium battery anode materials, in order to solve the problems of uneven density distribution, obvious anisotropy and insufficient thermal shock resistance caused by traditional unidirectional or bidirectional pressing while retaining the advantages of high efficiency and low cost of molding process.

[0007] To address the aforementioned technical problems, this application provides a method for multi-directional synchronous pressing of graphite crucibles for lithium battery anode materials, comprising the following steps: (1) Raw material preparation: Select graphite raw materials with particle sizes of 0-2 mm, 0-3 mm, and 5-25 mm, and asphalt, wherein the sulfur content of the graphite raw materials is ≤ 3%, the ash content is ≤ 0.5%, the volatile matter is < 1%, the fixed carbon is ≥ 98.5%, and the coking value of the asphalt is ≥ 50% and the softening point is ≥ 90℃; (2) Grinding and grading: Graphite raw materials with particle sizes of 0-2 mm and 0-3 mm are fed into Raymond mill and ground for 60-100 minutes respectively; graphite raw materials with particle sizes of 5-25 mm are fed into a large silo and crushed by a crusher; the ground and crushed materials are sent to a vibrating screen by an elevator and screened into the following particle size distribution according to mass percentage: 0-0.5 mm accounts for 32.9%, 0.5-1 mm accounts for 22.6%, 1-2 mm accounts for 25.2%, and 2-4 mm accounts for 19.3%; (3) Mixing: The sieved graphite raw materials of each grade are fed into the mixing machine via a belt conveyor with a large angle. After dry mixing for 40 minutes, the asphalt is injected into the mixing machine and wet mixed for 35 minutes at a temperature of 165℃±5℃ to obtain a paste. (4) Temperature equalization and weighing: The paste is sent to the temperature equalization pot by a belt conveyor with a large angle for temperature equalization treatment. After discharge, it is weighed according to the preset single weight of the crucible, and then put into the molding cavity of the crucible forming machine. (5) Multi-directional synchronous pressing: The crucible forming machine performs multi-directional synchronous static pressing on the paste in the molding cavity under a pressure of 20 MPa, and holds the pressure for 3 minutes before pushing the formed crucible blank out of the molding cavity. (6) Cooling and shaping: The formed crucible is cooled by water pipes to shape it, thus obtaining the green graphite crucible blank.

[0008] As a preferred embodiment, in a multi-directional synchronous pressing method for a graphite crucible for lithium battery anode materials, in step (2), the particle size control accuracy of the vibrating screen is ±0.1 mm, and the error of the particle size distribution ratio does not exceed ±2%.

[0009] As a preferred embodiment, in a multi-directional synchronous pressing method for a graphite crucible for lithium battery anode materials, in step (3), the dry mixing speed is 20-40 r / min and the wet mixing speed is 15-30 r / min.

[0010] As a preferred embodiment, in a multi-directional synchronous pressing method for a graphite crucible for lithium battery anode materials, in step (3), the amount of asphalt injected is 10%-20% of the total mass of the mixed powder.

[0011] As a preferred embodiment, a multi-directional synchronous pressing method for graphite crucibles used for lithium battery anode materials, in step (5), the multi-directional synchronous static pressing includes: simultaneously applying axial pressure and at least two radial pressures to the paste in the molding die cavity to achieve uniform density distribution of the graphite crucible wall and bottom.

[0012] The solution requires detailed explanation of a multi-directional synchronous pressing method for lithium battery anode materials using a graphite crucible, wherein the axial pressure is 5-10 MPa, the radial pressure is 10-15 MPa, and the total holding pressure is 20 MPa.

[0013] As a preferred embodiment, in a multi-directional synchronous pressing method for a graphite crucible for lithium battery anode materials, in step (5), the pressure fluctuation during the holding period does not exceed ±0.5 MPa.

[0014] As a preferred embodiment, in a multi-directional synchronous pressing method for graphite crucibles for lithium battery anode materials, in step (6), the water cooling adopts a zoned progressive spraying method, the cooling water temperature is 10-25℃, and the cooling time is 10-30 minutes, so that the surface temperature of the graphite crucible drops to below 60℃.

[0015] The solution requires further detailed explanation of a multi-directional synchronous pressing method for a graphite crucible for lithium battery anode materials. In step (1), the graphite raw material is petroleum coke-based or coal-based graphite, and the asphalt is coal tar pitch or petroleum tar pitch.

[0016] Compared with the prior art, the multi-directional synchronous pressing method for lithium battery anode materials using a graphite crucible provided by the present invention has at least the following beneficial effects: 1. This invention involves grinding or crushing three different graphite raw materials with varying particle sizes (0-2 mm, 0-3 mm, and 5-25 mm) and employing a specific mass percentage (0-0.5 mm ∶ 0.5-1 mm ∶ 1-2 mm ∶ 2-4 mm = 32.9 ∶ 22.6 ∶ 25.2 ∶ 19.3) to achieve the densest possible packing of coarse, medium, and fine particles. This gradation design significantly reduces interparticle porosity, thereby increasing the bulk density, flexural strength, and compressive strength of the pressed graphite crucible, thus extending its service life under high-temperature and highly corrosive environments.

[0017] 2. This invention employs a multi-directional synchronous static pressing process, pressing the paste within the molding die cavity under 20 MPa pressure. Compared to traditional unidirectional or bidirectional pressing methods, multi-directional synchronous pressing ensures the paste experiences uniform compressive stress throughout the molding die cavity, effectively preventing density differences between the bottom and sidewalls of the graphite crucible caused by stress concentration. The density difference between the wall and bottom of the pressed graphite crucible can be controlled within a set range, achieving uniform overall density and good isotropy of the graphite crucible. This results in more uniform thermal conductivity and thermal shock resistance during the graphitization process of lithium battery anode materials. Attached Figure Description

[0018] To more clearly illustrate the technical solution of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0019] Figure 1 A simplified flowchart of a method for multi-directional synchronous pressing of lithium battery anode materials using a graphite crucible, provided in an embodiment of this application. Detailed Implementation

[0020] To enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings.

[0021] The core of this application is to provide a multi-directional synchronous pressing method for graphite crucibles used in lithium battery anode materials. This method solves the problems of uneven density distribution, significant anisotropy, and insufficient thermal shock resistance caused by traditional unidirectional or bidirectional pressing, while retaining the advantages of high efficiency and low cost of the molding process.

[0022] Figure 1 A simplified flowchart of a multi-directional synchronous pressing method for lithium battery anode materials using a graphite crucible, provided in an embodiment of this application, is shown below. Figure 1 As shown.

[0023] Example 1 (1) Raw material preparation Graphite raw materials derived from petroleum coke were selected, with the mass ratio of 0-2 mm, 0-3 mm, and 5-25 mm graphite raw materials being 2:1:3. The graphite raw materials had the following specifications: sulfur content 2.5%, ash content 0.4%, volatile matter 0.7%, and fixed carbon 99.0%. Coal tar pitch was selected as the binder, with specifications including a coking value of 55% and a softening point of 95℃.

[0024] (2) Grinding and classification Graphite raw materials with particle sizes of 0-2 mm and 0-3 mm were fed into a Raymond mill and ground for 80 minutes. Graphite raw materials with particle sizes of 5-25 mm were fed into a large hopper and crushed to below 4 mm using a jaw crusher. The ground and crushed materials were then fed into a three-layer vibrating screen (screen apertures of 0.5 mm, 1 mm, 2 mm, and 4 mm) via a bucket elevator. The materials were then sieved by mass percentage as follows: 0-0.5 mm 32.9%, 0.5-1 mm 22.6%, 1-2 mm 25.2%, and 2-4 mm 19.3%. The particle size control accuracy of the vibrating screen was ±0.1 mm, and the error of the particle size distribution ratio was ±1.5%.

[0025] (3) Mixing and kneading The sieved graphite raw materials of various grades were fed into a Z-type twin-shaft mixer via a steep-angle belt conveyor and dry-mixed for 40 minutes at a speed of 30 r / min. Then, coal tar pitch was added, at a rate of 15% of the total mass of the mixed powder. The mixture was then wet-mixed at 165℃ for 35 minutes at a speed of 22 r / min to obtain a paste. Testing showed that the paste was uniform, free of dry powder particles, and exhibited good plasticity.

[0026] (4) Temperature equalization and weighing The paste is fed into a uniform temperature pot via a belt conveyor with a large inclination angle and uniformly treated at 160°C for 20 minutes. After discharge, the paste is automatically weighed according to the net weight of 25 kg per crucible and then put into the molding cavity of the crucible forming machine.

[0027] (5) Multi-directional synchronous suppression A multi-directional synchronous hydrostatic pressing machine is used. This equipment is equipped with an axial main hydraulic cylinder and four radial auxiliary hydraulic cylinders evenly distributed around the circumference. The pressing process begins by applying an axial pressure of 8 MPa to the paste in the molding cavity, simultaneously applying a radial pressure of 12 MPa, maintaining a total pressure of 20 MPa for 3 minutes. During the holding period, pressure fluctuations are controlled within ±0.3 MPa through real-time adjustment via a servo valve. After the holding period, the main hydraulic cylinder returns, and the ejector cylinder pushes the formed crucible blank out of the molding cavity.

[0028] (6) Cooling and shaping The formed crucible was transferred to a cooling chamber and subjected to zoned, progressive spray cooling: first, cooling water (15℃) was sprayed onto the upper part of the crucible for 3 minutes, then onto the middle part for 5 minutes, and finally onto the bottom for 7 minutes, for a total cooling time of 15 minutes. After cooling, the surface temperature of the crucible was 55℃, with no visible cracks, and the shape was well set.

[0029] In the actual pressing process, after cooling and shaping, the cooled graphite crucible blank can also be dried. (7) Drying treatment The cooled and shaped graphite crucible is dried at 200℃ for 4 hours to remove residual moisture, thus obtaining the graphite crucible green blank.

[0030] Example 2 (1) Raw material preparation Graphite raw materials from coal-based graphite were selected, with the mass ratio of 0-2 mm, 0-3 mm, and 5-25 mm particle sizes being 2:1:3. The graphite raw materials had the following specifications: sulfur content 2.5%, ash content 0.4%, volatile matter 0.7%, and fixed carbon 99.0%. Petroleum pitch was selected as the binder, and the coal tar pitch had the following specifications: coking value 52% and softening point 92℃.

[0031] (2) Grinding and classification Graphite raw materials with particle sizes of 0-2 mm and 0-3 mm were fed into a Raymond mill and ground for 100 minutes respectively. Graphite raw materials with particle sizes of 5-25 mm were fed into a large hopper and crushed to below 4 mm using a double-roll crusher. The ground and crushed materials were then fed into a three-layer vibrating screen (screen apertures of 0.5 mm, 1 mm, 2 mm, and 4 mm) via a bucket elevator, and separated by mass percentage as follows: 0-0.5 mm 32.9%, 0.5-1 mm 22.6%, 1-2 mm 25.2%, and 2-4 mm 19.3%. The particle size control accuracy of the vibrating screen was ±0.1 mm, and the error of the particle size distribution ratio was ±1.5%.

[0032] (3) Mixing and kneading The sieved graphite raw materials of various grades were fed into a Z-type twin-shaft mixer via a steep-angle belt conveyor and dry-mixed for 40 minutes at a speed of 20 r / min. Then, coal tar pitch was added, at a rate of 10% of the total mass of the mixed powder. The mixture was then wet-mixed at 170℃ for 35 minutes at a speed of 15 r / min to obtain a paste. Testing showed that the paste was uniform, free of dry powder particles, and exhibited good plasticity.

[0033] (4) Temperature equalization and weighing The paste is fed into a uniform temperature pot via a belt conveyor with a large inclination angle and uniformly treated at 160°C for 20 minutes. After discharge, the paste is automatically weighed according to the net weight of 25 kg per crucible and then put into the molding cavity of the crucible forming machine.

[0034] (5) Multi-directional synchronous suppression A multi-directional synchronous hydrostatic pressing machine is used. This equipment is equipped with an axial main hydraulic cylinder and four radial auxiliary hydraulic cylinders evenly distributed around the circumference. The pressing process begins by applying an axial pressure of 5 MPa to the paste in the molding cavity, simultaneously applying a radial pressure of 15 MPa, maintaining a total pressure of 20 MPa for 3 minutes. During the holding period, pressure fluctuations are controlled within ±0.5 MPa through real-time adjustment via a servo valve. After the holding period, the main hydraulic cylinder returns, and the ejector cylinder pushes the formed crucible blank out of the molding cavity.

[0035] (6) Cooling and shaping The formed crucible was transferred to a cooling chamber and subjected to zoned, progressive spray cooling: first, cooling water (10℃) was sprayed onto the upper part of the crucible for 5 minutes, then onto the middle part for 8 minutes, and finally onto the bottom for 7 minutes, for a total cooling time of 20 minutes. After cooling, the surface temperature of the crucible was 50℃, with no visible cracks, and the shape was well set.

[0036] In the actual pressing process, after cooling and shaping, the cooled graphite crucible blank can also be dried. (7) Drying treatment The cooled and shaped graphite crucible is dried at 200℃ for 4 hours to remove residual moisture, thus obtaining the graphite crucible green blank.

[0037] Example 3 (1) Raw material preparation Graphite raw materials derived from petroleum coke were selected, with the mass ratio of 0-2 mm, 0-3 mm, and 5-25 mm graphite raw materials being 2:1:3. The graphite raw materials had the following specifications: sulfur content 2.5%, ash content 0.4%, volatile matter 0.7%, and fixed carbon 99.0%. Coal tar pitch was selected as the binder, with specifications including a coking value of 55% and a softening point of 95℃.

[0038] (2) Grinding and classification Graphite raw materials with particle sizes of 0-2 mm and 0-3 mm were fed into a Raymond mill and ground for 80 minutes. Graphite raw materials with particle sizes of 5-25 mm were fed into a large hopper and crushed to below 4 mm using a jaw crusher. The ground and crushed materials were then fed into a three-layer vibrating screen (screen apertures of 0.5 mm, 1 mm, 2 mm, and 4 mm) via a bucket elevator. The materials were then sieved by mass percentage as follows: 0-0.5 mm 32.9%, 0.5-1 mm 22.6%, 1-2 mm 25.2%, and 2-4 mm 19.3%. The particle size control accuracy of the vibrating screen was ±0.1 mm, and the error of the particle size distribution ratio was ±1.5%.

[0039] (3) Mixing and kneading The sieved graphite raw materials of various grades were fed into a Z-type twin-shaft mixer via a steep-angle belt conveyor and dry-mixed for 40 minutes at a speed of 40 r / min. Then, coal tar pitch was added, at a rate of 20% of the total mass of the mixed powder. The mixture was then wet-mixed at 160℃ for 35 minutes at a speed of 30 r / min to obtain a paste. Testing showed that the paste was uniform, free of dry powder particles, and exhibited good plasticity.

[0040] (4) Temperature equalization and weighing The paste is fed into a uniform temperature pot via a belt conveyor with a large inclination angle and uniformly treated at 160°C for 20 minutes. After discharge, the paste is automatically weighed according to the net weight of 25 kg per crucible and then put into the molding cavity of the crucible forming machine.

[0041] (5) Multi-directional synchronous suppression A multi-directional synchronous hydrostatic pressing molding machine is used. This equipment is equipped with an axial main hydraulic cylinder and four radial auxiliary hydraulic cylinders evenly distributed around the circumference. The pressing process begins by applying an axial pressure of 10 MPa and a radial pressure of 10 MPa to the paste in the molding cavity, maintaining a total pressure of 20 MPa for 3 minutes. During the holding period, pressure fluctuations are controlled within ±0.2 MPa through real-time adjustment via a servo valve. After the holding period, the main hydraulic cylinder returns, and the ejector cylinder pushes the formed crucible blank out of the molding cavity.

[0042] (6) Cooling and shaping The formed crucible was transferred to a cooling chamber and subjected to zoned, progressive spray cooling: first, cooling water (25℃) was sprayed onto the upper part of the crucible for 3 minutes, then onto the middle part for 3 minutes, and finally onto the bottom for 4 minutes, for a total cooling time of 10 minutes. After cooling, the surface temperature of the crucible was 58℃, with no visible cracks, and the shape was well set.

[0043] In the actual pressing process, after cooling and shaping, the cooled graphite crucible blank can also be dried. (7) Drying treatment The cooled and shaped graphite crucible is dried at 200℃ for 4 hours to remove residual moisture, thus obtaining the graphite crucible green blank.

[0044] Comparative Example To verify the multi-directional synchronous pressing effect of the present invention, a comparative example was set up. The only difference between the comparative example and Example 1 is that step (5) adopts traditional unidirectional pressing (axial pressure only 20 MPa, holding pressure for 3 minutes, no radial pressure).

[0045] After the drying process in step (7) of Examples 1 to 3, and in the comparative example, the following steps are also included: the cooled and shaped graphite crucible is placed into an iron crucible. The bottom of the iron crucible is first covered with an 8cm thick layer of coke particles (as filler material, which serves to support, uniformly transfer heat, and prevent deformation). The graphite crucible is filled with coke particles around its perimeter and inside the graphite crucible and compacted. Then, refractory bricks and pressure sand are laid on top to seal the top and prevent oxidation. A certain pressure is applied. After the crucible is loaded, it is neatly arranged in the calcining furnace. After ignition, it undergoes 415 hours of heating, heat preservation, and cooling. After the crucible is taken out of the furnace, it is separated from the filler material and cleaned to obtain the finished graphite crucible.

[0046] Test results: The density of the comparative crucible wall was 1.58 g / cm³. 3 The bottom density is 1.73 g / cm³. 3 Density difference 0.15 g / cm³ 3 The crucible exhibited significant density stratification at the bottom and sidewalls, which easily led to deformation and cracking during subsequent high-temperature graphitization treatment, resulting in a yield of only 72%. However, testing showed that the density of the finished graphite crucible wall in Example 1 was 1.72 g / cm³. 3 The bottom density is 1.70 g / cm³. 3 Density difference 0.02 g / cm³ 3 The crucible has an outer diameter of 320 mm, an inner diameter of 260 mm, and a height of 500 mm, with a dimensional deviation of ≤±1 mm. The yield of the finished product in Example 1 can reach 96%. The wall density of the finished crucible in Example 2 is measured to be 1.70 g / cm³. 3 The bottom density is 1.68 g / cm³. 3 Density difference 0.02 g / cm³ 3 The crucible has an outer diameter of 320 mm, an inner diameter of 260 mm, and a height of 500 mm, with a dimensional deviation of ≤±1 mm. All performance characteristics meet the requirements for crucibles used in the graphitization of lithium battery anode materials. The yield of Example 2 can reach 94%. Testing showed that the wall density of the finished crucible in Example 3 is 1.74 g / cm³. 3 The bottom density is 1.72 g / cm³. 3 Density difference 0.02 g / cm³ 3 The compressive strength is increased by about 18% compared with the unidirectional pressing crucible. The outer diameter of the crucible is 320 mm, the inner diameter is 260 mm, the height is 500 mm, and the dimensional deviation is ≤±1 mm. All performances meet the requirements of crucibles for graphitization of lithium battery anode materials. The yield of Example 3 can reach 95%, which proves that the multidirectional synchronous pressing method of the present invention significantly improves the uniformity of crucible density and yield.

[0047] Table 1. Graphite crucible parameters for each embodiment. Other embodiments of this application will readily occur to those skilled in the art upon consideration of the specification and practice of the application disclosed herein. This application is intended to cover any variations, uses, or adaptations of this application that follow the general principles of this application and incorporate common knowledge or customary techniques in the art disclosed herein. The specification and examples are to be considered exemplary only, and the true scope of this application is indicated by the claims.

[0048] It should be understood that this application is not limited to the precise structure described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The embodiments of this application described above do not constitute a limitation on the scope of protection of this application.

Claims

1. A method for multi-directional synchronous pressing of lithium battery anode materials using a graphite crucible, characterized in that, Includes the following steps: (1) Raw material preparation: Select graphite raw materials with particle sizes of 0-2 mm, 0-3 mm, and 5-25 mm, and asphalt, wherein the sulfur content of the graphite raw materials is ≤ 3%, the ash content is ≤ 0.5%, the volatile matter is < 1%, the fixed carbon is ≥ 98.5%, and the coking value of the asphalt is ≥ 50% and the softening point is ≥ 90℃; (2) Grinding and grading: Graphite raw materials with particle sizes of 0-2 mm and 0-3 mm are fed into Raymond mill and ground for 60-100 minutes respectively; graphite raw materials with particle sizes of 5-25 mm are fed into a large silo and crushed by a crusher; the ground and crushed materials are sent to a vibrating screen by an elevator and screened into the following particle size distribution according to mass percentage: 0-0.5 mm accounts for 32.9%, 0.5-1 mm accounts for 22.6%, 1-2 mm accounts for 25.2%, and 2-4 mm accounts for 19.3%; (3) Mixing: The sieved graphite raw materials of each grade are fed into the mixing machine via a belt conveyor with a large angle. After dry mixing for 40 minutes, the asphalt is injected into the mixing machine and wet mixed for 35 minutes at a temperature of 165℃±5℃ to obtain a paste. (4) Temperature equalization and weighing: The paste is sent to the temperature equalization pot by a belt conveyor with a large angle for temperature equalization treatment. After discharge, it is weighed according to the preset single weight of the crucible, and then put into the molding cavity of the crucible forming machine. (5) Multi-directional synchronous pressing: The crucible forming machine performs multi-directional synchronous static pressing on the paste in the molding cavity under a pressure of 20 MPa, and holds the pressure for 3 minutes before pushing the formed crucible blank out of the molding cavity. (6) Cooling and shaping: The formed crucible is cooled by water pipes to shape it, thus obtaining the green graphite crucible blank.

2. The method for multi-directional synchronous pressing of lithium battery anode materials using a graphite crucible according to claim 1, characterized in that, In step (2), the particle size control accuracy of the vibrating screen is ±0.1 mm, and the error of the particle size distribution ratio does not exceed ±2%.

3. The multi-directional synchronous pressing method for lithium battery anode materials using a graphite crucible according to claim 1, characterized in that, In step (3), the dry mixing speed is 20-40 r / min, and the wet mixing speed is 15-30 r / min.

4. The multi-directional synchronous pressing method for lithium battery anode materials using a graphite crucible according to claim 1, characterized in that, In step (3), the amount of asphalt injected is 10%-20% of the total mass of the mixed powder.

5. The multi-directional synchronous pressing method for lithium battery anode materials using a graphite crucible according to claim 1, characterized in that, In step (5), the multi-directional synchronous static pressing includes: simultaneously applying axial pressure and at least two radial pressures to the paste in the molding die cavity to achieve a uniform density distribution on the graphite crucible wall and bottom.

6. The multi-directional synchronous pressing method for lithium battery anode materials using a graphite crucible according to claim 5, characterized in that, The axial pressure is 5-10 MPa, the radial pressure is 10-15 MPa, and the total holding pressure is 20 MPa.

7. The method for multi-directional synchronous pressing of lithium battery anode materials using a graphite crucible according to claim 1, characterized in that, In step (5), the pressure fluctuation during the pressure holding period shall not exceed ±0.5 MPa.

8. The method for multi-directional synchronous pressing of lithium battery anode materials using a graphite crucible according to claim 1, characterized in that, In step (6), the water cooling adopts a zoned progressive spraying method, the cooling water temperature is 10-25℃, and the cooling time is 10-30 minutes, so that the surface temperature of the graphite crucible drops to below 60℃.

9. The method for multi-directional synchronous pressing of lithium battery anode materials using a graphite crucible according to claim 1, characterized in that, In step (1), the graphite raw material is petroleum coke-based or coal-based graphite, and the asphalt is coal tar pitch or petroleum tar pitch.